2016
DOI: 10.1186/s12864-016-3271-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNAs in Humulus lupulus using high-throughput sequencing and their response to Citrus bark cracking viroid (CBCVd) infection

Abstract: BackgroundHop (Humulus lupulus L.) plants are grown primarily for the brewing industry and have been used as a traditional medicinal herb for a long time. Severe hop stunt disease caused by the recently discovered Citrus bark cracking viroid (CBCVd) is one of the most devastating diseases among other viroid infections in hop. MicroRNAs (miRNAs) are a class of non-coding small RNAs that play important roles in gene expression regulation. To identify miRNAs in hop and their response to CBCVd-infection, two small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 79 publications
(112 reference statements)
1
32
0
Order By: Relevance
“…The hop plant is infected by several viroids during its growth and development such as Hop stunt viroid (HSVd) and Apple fruit crinkle viroid (AFCVd) [ 16 ], Hop latent viroid (HLVd), and the recently reported Citrus bark cracking viroid (CBCVd) member of the genus Cocadviroid in the family Pospiviroidae. [ 17 , 18 ]. Among them, the CBCVd infection is the most aggressive causing dramatic morphological and anatomical changes, which include leaf epinasty, yellowing, premature flowering, and a reduction in cone size, dry root rotting, stunted growth, and dieback [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hop plant is infected by several viroids during its growth and development such as Hop stunt viroid (HSVd) and Apple fruit crinkle viroid (AFCVd) [ 16 ], Hop latent viroid (HLVd), and the recently reported Citrus bark cracking viroid (CBCVd) member of the genus Cocadviroid in the family Pospiviroidae. [ 17 , 18 ]. Among them, the CBCVd infection is the most aggressive causing dramatic morphological and anatomical changes, which include leaf epinasty, yellowing, premature flowering, and a reduction in cone size, dry root rotting, stunted growth, and dieback [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest viroid discovered on hop is CBCVd, which causes the most aggressive symptoms among all 4 hop viroids. Infected plants show the first symptoms 4 months after infection: severe stunting after first dormancy and complete dieback in 3–5 years [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frameshift mutation in MED17, MED18 and MED20 subunits leads to the reduced accumulation of miRNAs, indicating their crucial role in miRNA biogenesis [44]. We have already shown that CBCVd infection can significantly alter the expression profile of miRNAs in hop [45]. The upregulation of MED17 and MED18 in CBCVd-infected hop suggested their plausible involvement in the modulation of miRNA expression in viroid pathogenesis.…”
Section: Resultsmentioning
confidence: 89%